Waqf Logistics: An Exploratory Study of its Existence and Implementation - Nazry bin Yahya (Universitas YARSI, 2022)
Waqf logistics is already in practice around the globe! However not many people understand about the existence of such waqf branch because the concept is very niche that no academic paper has explored the subject at all. Due to that, waqf logistics practices has been ongoing for years without anyone able to extract such activity. One of the well-known examples of waqf logistics is the case of Larkin Sentral, in Malaysia. Hearse services and warehouses are some of the other examples of waqf logistics activities that has never been cited. There are also very strong possibilities that waqf logistics is in practice at various waqf cities, waqf plantations and waqf manufacturing setups around the globe because these activities require the movement of goods (MOG) and movement of people (MOP). This exploratory paper aims to establish the general principles of waqf logistics for the benefit of the future researchers and implementers.